Customer orientation and success in introduction of new products: an empirical study in an emerging economy. Issue 2 (1st October 2019) - Jiang, Wanxing; Li, Ji; Yan, Haifeng; Li, Hao; Chen, Mengyuan
Abstract : Purpose: The purpose of this paper is to investigate whether, when and how customer orientation may contribute to success in introduction of new products (SINP). Design/methodology/approach: With a multi-phase and multi-source data collection approach, this study tested the proposed theoretical model by applying multiple regression with SPSS Process Macro. Findings: Customer orientation positively influences cross-functional integration (CFI), which in turn facilitates SINP; a firm's new product introduction (NPI) strategy moderates customer orientation–CFI link. Originality/value: This study empirically tests whether, why and when customer orientation may contribute to SINP. By suggesting the important role of customer orientation in improving SINP, the mediating effect of CFI and the moderating effect of NPI strategy, the current study should enrich the extant literature on customer orientation, CFI and NPI.